UNIVERSAL PRINCIPLES OF ARCHITECTURE 100 architectural archetypes, methods, conditions, relationships, and imaginaries - Frankowski, Nathalie; Garcia, Cruz, 1983- (ROCKPORT PUBLISHERS INC, 2023)
Universal Principles of Architecture is a concise, visual introduction to 100 of the most fundamental elements of architecture.